Desigualdades de gênero em tempo de trabalho pago e n\~ao pago no Brasil, 2013 - Luana Sim\~oes Pinheiro; Marcelo C. Medeiros (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– We examine gender inequalies in time use in Brazil by decomposing the total time employed in work in paid (market) and unpaid work (domestic). Data comes from the 2013 National Household Survey, Pnad. We found large inequalities within the subgroups of men and women. Most inequality within these groups is related to the polarization between working or not. Female work, both paid and unpaid, is what contributes more to total inequality in society. The domestic work of men is not common and, as a consequence, contributes little to total inequality. The main determinants of the gender differential in working hours are the proportion of people who do some paid work and the duration of unpaid work. The sexual division of labor is not characterized by a mirroring of activities. Therefore, women invariably work more than men, even when within group inequalities are taken into account.
Keywords: J22; 330; time use; housework; household labor; sexual division of labor